HUBUNGAN PARITAS DAN DUKUNGAN SUAMI DENGAN PENGGUNAAN ALAT KONTRASEPSI INTRA UTERINE DEVIDE (IUD) DI KLINIK PRATAMA HANNA KASIH TAHUN 2020 - Netty Herawaty Br Sembiring; Febriana Sari; Rosmani Sinaga (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Based on data from Indonesia's Health Profile in 2016, Indonesia has a population of 258,704,986 people. Indonesia still ranks fourth with the largest population in the world after America, India and China. The total population of Indonesia in 2019 is estimated at 268,074,565 people, consisting of 117,674,363 urban residents and 150,400,202 rural residents. One of the programs to reduce population growth in realizing a family planning program (KB). The results of the prevalence of family planning in Indonesia based on the 2015 Fertile Age Couples Monitoring Survey reached 65.4% with the IUD method, which is still very low (4.7%). This study aims to determine the relationship between parity and husband's support with the use of IUDs at the Hanna Kasih Primary Clinic in 2020. The population in this study were acceptors who currently use IUD KB and have used IUD KB but now choose other types of family planning. The number of samples in this study were taken by total sampling, amounting to 30 people. The results obtained in this study from 30 respondents the majority were Scundipara, namely 11 (36.7%) respondents. Based on husband's support, the majority received positive husband support, namely 22 (73.3%). Based on the bivariate analysis, there is a significant relationship between parity and husband's support with the use of IUD contraceptives at the Pratama Hana Kasih clinic in 2020, with p value for parity <0.05 (p = 0.015) and for husband support with p value <0.05. (p = 0.000). It is hoped that the head of the Pratama Clinique Hanna Kasih will continue to provide support in the selection of the IUD contraceptive and the husband will continue to provide positive support for the wife to continue to use the IUD contraceptive device.